1998
DOI: 10.1021/bi980777t
|View full text |Cite
|
Sign up to set email alerts
|

SecB Binds Only to a Late Native-like Intermediate in the Folding Pathway of Barstar and Not to the Unfolded State

Abstract: SecB is a cytosolic, tetrameric chaperone of Escherichia coli which maintains precursor proteins in a translocation competent state. We have investigated the effect of SecB on the refolding kinetics of the small protein barstar in 1 M guanidine hydrochloride at pH 7.0 and 25 degreesC using fluorescence spectroscopy. We show that SecB does not bind either the native or the unfolded states of barstar but binds to a late near-native intermediate along the folding pathway. For barstar, polypeptide collapse and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Thus, the data is consistent with a model that the B-chain is bound on the surface of the chaperone SecB in a flexible extended state. In certain cases it has been shown that SecB binds to partially folded conformations of proteins such as ␣-lactalbumin and barstar (8,10). In the present work we suggest that the bound conformation is an extended conformation.…”
Section: Thermodynamic Coupling Model Of B-chain Dissociation Bysupporting
confidence: 52%
See 2 more Smart Citations
“…Thus, the data is consistent with a model that the B-chain is bound on the surface of the chaperone SecB in a flexible extended state. In certain cases it has been shown that SecB binds to partially folded conformations of proteins such as ␣-lactalbumin and barstar (8,10). In the present work we suggest that the bound conformation is an extended conformation.…”
Section: Thermodynamic Coupling Model Of B-chain Dissociation Bysupporting
confidence: 52%
“…SecB purification was done as reported previously (8). The purified protein was estimated to be 99% pure by SDS-polyacrylamide gel electrophoresis as detected by silver staining (16) and analytical gel filtration high Performance liquid chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SecB purification was done as reported previously (6). The purified protein was estimated to be 99% pure by SDS-polyacrylamide gel electrophoresis as detected by silver staining (28) and analytical gel filtration high performance liquid chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…For some proteins the translocationcompetent state contains significant secondary and tertiary structure (4). Studies on the model protein substrate, barstar, revealed that SecB does not bind the folded or unfolded state but traps a near native-like molten globule state (6). SecB has also been shown to bind partially folded states of lactalbumin (9).…”
mentioning
confidence: 99%